Cancer immunotherapy targeting neoantigens - Lu, Yong-Chen (Semin Immunol, 2015)
Neoantigens are antigens that are encoded by tumor-specific mutated genes. Studies in the past few years have suggested a key role for neoantigens in cancer immunotherapy. Here we review the discoveries of neoantigens in the past two decades and the current advances in neoantigen identification. We also discuss the potential benefits and obstacles to the development of effective cancer immunotherapies targeting neoantigens.